Plant response to solar ultraviolet-B radiation in a southern South American Sphagnum peatland - Searles, Peter Stoughton; Flint, Stephan D.; Diaz, Susana Beatriz; Rousseaux, Maria Cecilia; Ballare, Carlos Luis; Caldwell, Martyn M. (Journal of Ecology)
1. Plant growth and pigmentation of the moss Sphagnum magellanicum and the vascular plants Empetrum rubrum, Nothofagus antarctica and Tetroncium magellanicum were measured under near-ambient (90% of ambient) and reduced (20%) ultraviolet-B (UV-B) radiation for three growing seasons in a Sphagnum peatland in Tierra del Fuego, Argentina (55°S). 2. Reduction of solar UV-B increased height growth but decreased volumetric density in S. magellanicum so that biomass production was not influenced during the 3 years. The morphology of vascular plants tended not to respond to UV-B reduction. 3. A 10-20% decrease in UV-B-absorbing compounds occurred in T. magellanicum under solar UV-B reduction. No effects were seen on chlorophyll or carotenoids in S. magellanicum, although, for UV-B-absorbing compounds, a significant interaction between UV-B and year suggests some response to solar UV-B reduction. 4. The climate-related growth of the dwarf shrub E. rubrum was assessed retrospectively by correlating an 8-year record of annual stem elongation with macroclimatic factors including solar UV-B and visible radiation, precipitation and temperature. 5. No significant negative correlations were found between annual E. rubrum stem elongation and ambient solar UV-B, the ratio of UV-B: visible radiation, or the 305-nm: 340-nm irradiance ratio for an 8-year record (1990-91 to 1997-98), nor was stem elongation affected by solar UV-B reduction in our experimental field plots after 3 years. 6. The role of solar UV-B radiation on plant growth in Sphagnum peatlands in Tierra del Fuego, Argentina, is likely to depend on the severity of stratospheric ozone depletion over the next several decades. The increases in ambient solar UV-B associated with ozone depletion over the last 20 years are less than the difference between our radiation treatments. Therefore, providing that the ozone layer substantially recovers by the middle of this century, only modest effects of increased solar UV-B on plant growth may be expected. Fil: Searles, Peter ...